Pengembangan Game Pembelajaran Menggunakan Platform Wordwall pada Tema 3 Makananan Sehat Kelas V Sekolah Dasar - Wisry Dona Ernita; Novrianti Novrianti; Zuwirna Zuwirna; Ade Meldi (Departement of Mathematics Education, 2023)
With the current learning conditions that are increasingly advanced, students need supporting learning media, namely flexible learning media that students can access without having to be in the classroom. However, the use of learning media is still lacking and limited, especially technology-based learning media such as learning games. Learning games using Wordwall can help teachers develop instructional media that students can practically access outside of the classroom. The goal achieved in this study is to determine the feasibility and practicality of the learning game. This type of research is Research and Development (R&D). The development model used in this study is the ASSURE model which has 6 stages of development, namely analyze learner, state objectives, select instructional method, utilize media and materials, require learner participation, evaluate and revise. The results of the validity test of learning game media by media expert I are categorized as